Application of The Jungle of Phytagoras Discovery Learning Method Assisted with The Nearpod Application - Sakinah, Zulfatus; Rahadi, Rustanto; Sulandra, I Made (PRISMA, 2024)
The application of this learning aims to improve the quality of students by developing learning media. The teaching media used for the lesson is the Nearpod application for grade 8 Pythagorean material in middle school in accordance with the implementation plan for mathematics learning in junior high school. The approach used in this learning is Discovery Learning. In this case, the teacher will develop one of the teaching materials in the form of learning media using the Discovery Learning approach. Based on the results of the presentation above, the teacher has carried out open media teaching using the Discovery Learning method for the Pythagorean theorem material for grade 8 junior high school which aims to improve student learning outcomes. The subject of this teaching is grade 8 students. The object of this teaching is to create mathematics teaching media using the Discovery Learning approach in understanding the Pythagorean theorem material. This teaching was carried out to determine student learning outcomes after using Android-based mathematics teaching media with the Discovery Learning approach regarding Pythagorean theorem material for grade 8 junior high school students. There are 4 stages in this learning, namely planning, action, observation and reflection.